Sekolah Perempuan Perkebunan Berbasis Potensi Alam Untuk Mengembangkan Life-Skill Masyarakat Desa Harjomulyo - (indonesia), Supeno; (indonesia), Alifiah Putri; (indonesia), Gloria Sagita Harimisa; (indonesia), Aisyah Emelia Ismawati; (indoensia), Zulfa Nishom Fahmi (Fakultas Pertanian_Universitas Tidar, 2024)
Harjomulyo Village, located in Jember district, covers 38.44 km2 and is 700 meters above sea level. Given its geographical location, Harjomulyo has promise in the agricultural and plantation sectors, which is aided by the presence of wadung plantations that surround the majority of the communities. Despite this promise, the author believes that some issues, particularly those concerning education, life skills, and economics, require further discussion. Based on the problem identification, the remedy was bundled into the